The Return of al-Qaida: Current developments in international terrorism and their consequences for Europe - Guido Steinberg (Stiftung Wissenschaft und Politik (SWP), 2007)
The al-Qaida leadership around Usama Bin Laden and his deputy Aiman al-Zawahiri used the year 2007 for an unprecedented public relations campaign. Never before had leading representatives of the organization been seen and heard so frequently in video and audio messages. The campaign's climax was a videotape from early September 2007 in which Bin Laden himself appeared on film for the first time since 2004 sharply criticizing the war in and the presence in Afghanistan. This media resurgence raises the question whether al-Qaida's intensified activities represent desperate attempts to gain attention in the mass media and thus constitute signs of decline, or whether they should be interpreted as signs of a renewed strength that is being further reinforced through the organization's increased utilization of the media
Keywords: 320